2021
DOI: 10.1002/advs.202100292
|View full text |Cite
|
Sign up to set email alerts
|

Programmable Unlocking Nano‐Matryoshka‐CRISPR Precisely Reverses Immunosuppression to Unleash Cascade Amplified Adaptive Immune Response

Abstract: Immune checkpoint blockade (ICB) is an attractive option in cancer therapy, but its efficacy is still less than expected due to the transient and incomplete blocking and the low responsiveness. Herein, an unprecedented programmable unlocking nano-matryoshka-CRISPR system (PUN) targeting programmed cell death ligand 1 (PD-L1) and protein tyrosine phosphatase N2 (PTPN2) is fabricated for permanent and complete and highly responsive immunotherapy. While PUN is inert at normal physiological conditions, enzyme-abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 38 publications
0
49
0
Order By: Relevance
“…In addition, the degradation of HA by hyaluronidase triggers a charge reversion promoting the endosomal escape. [ 37 ] The fusion peptides, T22‐NLS can specifically combine with CXCR4 overexpressed on cancer cells to promote cellular uptake by the T22 sequence, [ 38 , 39 ] and enhance nucleus translocation by the NLS sequence. [ 40 ] With the combination of these functional components, the multifunctional delivery vector can specifically deliver the geneediting plasmid to cell nuclei to effectively mediate CXCR4 knockout.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the degradation of HA by hyaluronidase triggers a charge reversion promoting the endosomal escape. [ 37 ] The fusion peptides, T22‐NLS can specifically combine with CXCR4 overexpressed on cancer cells to promote cellular uptake by the T22 sequence, [ 38 , 39 ] and enhance nucleus translocation by the NLS sequence. [ 40 ] With the combination of these functional components, the multifunctional delivery vector can specifically deliver the geneediting plasmid to cell nuclei to effectively mediate CXCR4 knockout.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, they developed a delivery system that can respond to enzymes and oxidative stress in the tumor environment to release the Cas9 plasmid, which can deplete the PD-L1 and protein tyrosine phosphatase N2 genes to achieve highly effective immunotherapy. [185] Moreover, Liu et al constructed a multi-stage transformable MDNP NP for dCas9-miR-524 pDNA delivery. [158] The core of MDNP is a cationic polyplex of phenylboronic acid (PBA) modified polyethyleneimine (PEI-PBA) and plasmid, while the shell is a layer of negatively charged 2,3-dimethylmaleic anhydride (DMMA) modified PEG-bpolylysine.…”
Section:  Cationic Polymers-based Delivery Systems Pcasmentioning
confidence: 99%
“…The study by Yang et al found that successful nuclear localization of CRISPR/Cas9 ensured efficient destruction of PD-L1 and PTPN2. Inhibition of PTPN2 can alleviate the inhibition of the JAK/STAT pathway and promote tumor susceptibility to CD8+ T cells dependent on IFN-γ, thereby further amplifying the adaptive immune response ( 38 ). Therefore, the combination of CRISPR/Cas9 technology with tumor immunotherapy has great potential for development.…”
Section: Crispr/cas9 In Tumor Immunitymentioning
confidence: 99%
“…Programmable unlockable nanoencapsulation CRISPR technology (PUN) has hierarchical response characteristics. PUN mitigates inhibition of the JAK/STAT pathway by knocking out the protein tyrosine phosphatase PTPN2 in tumor cells, which relies on IFN-γ to promote antigen presentation and growth inhibition, further amplifying adaptive immunity to PD-L1 blockade ( 38 ). The PI3K-AKT signaling pathway is mainly involved in regulating the glycolysis process of immune cells ( 72 ).…”
Section: Indirect Regulation Of Pd-1/pd-l1 By Crispr/cas9mentioning
confidence: 99%